AKTUALISASI IMPLEMENTASI KEBIJAKAN PENDIDIKAN PADA MADRASAH SWASTA DI SULAWESI SELATAN - Abdul Rahman Halim (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2008)
This research is aimed out implementation of govern-ment policy toward private Islamic schools before the role UU SPN No. 20 Year 2003. In reality, the policy of government did not run effectively, even it did not give advantages for private Islamic school, because the application is restricted to curriculum development. The Government has tried to perform several Islamic schools in order to be followed by private Islamic schools such as state Islamic schools, Islamic school for Islamic program, integrated school and so on. How ever, the Islamic private schools cannot run together with state schools because they face problem on financial and facilities of educational standard.